His wedding day revenge - Lawrence, Kim, 1938- (Harlequin presents, 2024)
Jane fled her wedding day when she discovered that she couldn't give Draco what he wanted--a family. Now she finds herself back in his world, hiding secrets old and new. Though their burning passion might demand a second chance, does Draco want to reclaim her...or does he want payback?